EFL classroom engagement to enhance communicative skills for ninth graders in a virtual environment. - Roldán Andrade, Erick Edward (2023)
The present research project aimed to determine the way that engagement strategies in EFL classes can enhance students’ communicative skills while learning in a virtual environment. The research had a qualitative approach establishing two groups. The first one consisted of ten students who were interviewed using a focus group technique, while the second involved two teachers interviewed individually. In both cases, a bank of seven open-ended questions was used. The interviews were conducted via a virtual meeting. As a result of the data collection, it was possible to gain a better understanding of the participant’s perspectives on the way engagement works within a virtual environment thereby enhancing their communicative skills. The analysis concludes that motivation and classroom engagement play a crucial role in English language learning, for which it is required to combine interactive activities such as real-life scenarios, use of up-to-date digital tools, and feedback. The implications of this study are significant for EFL teachers, particularly as virtual environments have become a normalized activity since the COVID-19 pandemic